Novel perovskite battery and preparation method thereof
By introducing antireflective coatings and equivalent refractive layers into perovskite solar cells, the problem of high solar reflectivity in perovskite solar cells is solved, enabling efficient utilization of light within the cells and improving power generation efficiency.
Patent Information
- Application Number
- CN202511472477.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2026-01-13
AI Technical Summary
Existing perovskite solar cells suffer from severe reflection problems before sunlight reaches the perovskite layer, leading to a decrease in the efficiency of photovoltaic cell systems.
In perovskite solar cells, antireflection film stacks and equivalent refractive layers are introduced. The antireflection film stacks are correlated with the absorption spectrum range of the perovskite layer, increasing the effective light transmittance. The equivalent refractive layer is correlated with the refractive index between the glass substrate and the hole transport layer, reducing interface reflection loss.
By designing antireflective coating layers and an equivalent refractive layer, the utilization rate of light within the battery is significantly improved, increasing the battery's power generation efficiency by approximately 5%-8%.
Smart Images

Figure CN121335343A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of solar cell technology, and in particular relates to a novel perovskite solar cell and its preparation method. Background Technology
[0002] In terms of structural design, perovskite solar cells mainly have three types: conventional, inverted, and mesoporous structures. Different companies may have different technical solutions, but all three structures include a top electrode, an electron transport layer, a perovskite layer, a hole transport layer, and a bottom electrode layer. In the conventional structure, the electron transport layer sits atop the bottom electrode layer; sunlight passes through the bottom electrode layer, then through the electron transport layer, and finally to the perovskite layer. In the inverted structure, the hole transport layer sits atop the bottom electrode layer; sunlight passes through the bottom electrode layer, then through the hole transport layer, and finally to the perovskite layer. However, regardless of the conventional or inverted structure, sunlight undergoes significant reflection before reaching the perovskite absorption layer, leading to a decrease in the system efficiency of the photovoltaic cell. Summary of the Invention
[0003] This application provides a novel perovskite solar cell and its fabrication method. Compared with the existing structure, an antireflection film stack and an equivalent refractive layer are added. The antireflection film stack increases the absolute amount of effective light entering the cell, while the equivalent refractive layer reduces the interface reflection loss of the perovskite solar cell, ensuring that incident light passing through the glass substrate penetrates to the perovskite layer without significant loss. Through the superposition of these two designs, the utilization rate of light in the cell can be effectively improved, thereby improving the power generation efficiency of the cell.
[0004] In a first aspect, this application provides a novel perovskite solar cell, comprising, sequentially arranged, an antireflection film stack, a glass substrate, an equivalent refractive layer, a hole transport layer, a perovskite layer, an electron transport layer, and a top electrode. The antireflection spectral range of the antireflection film stack is correlated with the absorption spectral range of the perovskite layer. The antireflection film stack is used to construct a refractive index transition between air and the glass substrate, increasing the transmittance of effective light within the absorption spectral range in natural light through a first interface, where the first interface is the interface between the antireflection film stack and the glass substrate. The target equivalent refractive index of the equivalent refractive layer is correlated with the first refractive index of the glass substrate and the second refractive index of the hole transport layer. The equivalent refractive layer is used to construct a refractive index transition between the glass substrate and the hole transport layer, reducing the reflectivity of incident light through a second interface, where the incident light is light that passes through the glass substrate and enters the equivalent refractive layer. The second interface is the interface between the equivalent refractive layer and the hole transport layer.
[0005] Secondly, this application provides a method for preparing a novel perovskite solar cell as described in the first aspect, the method comprising: performing flat cleaning and drying on a glass substrate; and depositing (SiO2+(Si3N4+SiO2)) on the front side of the glass substrate. n A (SiO2+SiON) film is formed to create an antireflective coating layer; a (SiO2+SiON) film is deposited on the reverse side of the glass substrate. x A Nb₂O₅ + ITO film is formed to create an equivalent refractive layer. The glass substrate with the above coating is then subjected to P1 laser scribing to form the P1 scribing lines for a novel perovskite solar cell. The glass substrate with the P1 scribing lines is then cleaned, and NiO is deposited on the equivalent refractive layer. y A hole transport layer is formed; after the hole transport layer is deposited, the light transmittance of the current perovskite solar cell in the absorption spectrum range is tested; if the light transmittance is greater than or equal to the preset transmittance, a perovskite layer is deposited on the hole transport layer; an electron transport layer is deposited on the perovskite layer; a P2 laser scribing is performed on the glass substrate after the electron transport layer is deposited; a top electrode is fabricated on the electron transport layer; a P3 laser scribing and a P4 laser edge cleaning are performed sequentially on the glass substrate after the top electrode is fabricated; a photovoltaic module is encapsulated on the glass substrate after the P4 laser edge cleaning to obtain a novel perovskite solar cell.
[0006] As can be seen, in this embodiment, the novel perovskite solar cell includes an antireflection film stack, a glass substrate, an equivalent refractive layer, a hole transport layer, a perovskite layer, an electron transport layer, and a top electrode arranged sequentially. The antireflection spectral range of the antireflection film stack is related to the absorption spectral range of the perovskite layer. The antireflection film stack is used to construct a refractive index transition between air and the glass substrate, increasing the transmittance of effective light within the absorption spectral range of natural light through a first interface, which is the interface between the antireflection film stack and the glass substrate. The target equivalent refractive index of the equivalent refractive layer is related to the first refractive index of the glass substrate and the second refractive index of the hole transport layer. The equivalent refractive layer is used to construct a refractive index transition between the glass substrate and the hole transport layer, reducing the reflectivity of incident light through a second interface, where the incident light is the light that passes through the glass substrate and enters the equivalent refractive layer. The second interface is the interface between the equivalent refractive layer and the hole transport layer. As can be seen, compared with the existing structure, this application increases the absolute amount of effective light entering the battery by stacking antireflective coatings. At the same time, it reduces the interface reflection loss of the perovskite battery by using an equivalent refractive layer, ensuring that incident light passing through the glass substrate can penetrate to the perovskite layer without significant loss. Through the superposition of these two designs, the utilization rate of light in the battery can be effectively improved, thereby improving the power generation efficiency of the battery. Attached Figure Description
[0007] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0008] Figure 1 A conventional perovskite solar cell structure provided in this application embodiment; Figure 2 A comparison diagram of the EQE and optical transmittance of the perovskite material before and after antireflection treatment for conventional perovskite solar cells provided in the embodiments of this application; Figure 3 This is a schematic diagram of the structure of a novel perovskite solar cell provided in an embodiment of this application; Figure 4 This is a schematic diagram of the optical path of a novel perovskite solar cell provided in an embodiment of this application; Figure 5 This is a schematic diagram of the optical path of a conventional perovskite solar cell provided in an embodiment of this application; Figure 6 A comparison diagram of the EQE and optical transmittance of the perovskite material before and after antireflection treatment for the novel perovskite solar cell provided in the embodiments of this application; Figure 7 A schematic flowchart illustrating the fabrication method of the novel perovskite solar cell provided in this application embodiment; Figure 8 This is a schematic diagram of the equivalent refractive layer and antireflective coating stack provided in the embodiments of this application. Detailed Implementation
[0009] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0010] In terms of structural design, perovskite solar cells mainly have three types: conventional, inverted, and mesoporous structures. Different companies may have different technical solutions, but all three structures include a top electrode, an electron transport layer, a perovskite layer, a hole transport layer, and a bottom electrode layer. In the conventional structure, the electron transport layer sits atop the bottom electrode layer; sunlight passes through the bottom electrode layer, then through the electron transport layer, and finally to the perovskite layer. In the inverted structure, the hole transport layer sits atop the bottom electrode layer; sunlight passes through the bottom electrode layer, then through the hole transport layer, and finally to the perovskite layer. However, regardless of the conventional or inverted structure, sunlight undergoes significant reflection before reaching the perovskite absorption layer, leading to a decrease in the system efficiency of the photovoltaic cell.
[0011] To address the sunlight reflection problem in perovskite photovoltaic cells, existing technologies improve transmittance by applying antireflection coatings. A typical perovskite cell structure is shown below. Figure 1 , Figure 1 This application provides a conventional perovskite solar cell structure, which includes, in sequence, an antireflection film, a glass substrate, a bottom electrode, a hole transport layer, a perovskite layer, an electron transport layer, and a top electrode. The antireflection film includes an antireflection film layer, a PET carrier, and an adhesive film layer. However, in reality, the antireflection film suffers from a mismatch between its antireflection spectrum and absorption spectrum. For example, perovskite materials with a band gap of 1.48 eV-1.56 eV were selected for experimental testing, and the test data are shown below. Figure 2 , Figure 2 The graph shows a comparison of the EQE and optical transmittance of the perovskite material before and after anti-reflection treatment in the conventional perovskite solar cells provided in this application embodiment. The spectral absorption of the material peaks at around 770 nm and drops rapidly at around 800 nm. Compared with the material absorption under the baseline condition (perovskite solar cell without anti-reflection treatment), after optical anti-reflection treatment of the substrate glass, the optical transmittance in the 400 nm-800 nm range increased by an average of 2.52%. However, compared with the perovskite device efficiency under the baseline condition, it decreased by 2.01%. The main reason is that in the 400 nm-650 nm range after anti-reflection treatment, the anti-reflection film has high transmittance, but the light transmitted in this part is not well absorbed by the material. Therefore, the external quantum efficiency (EQE) is relatively low in the 400 nm-650 nm range. At the same time, in the 650 nm-800 nm range, the transmittance of the substrate decreases, resulting in a decrease in the number of photons transmitted through the substrate in sunlight. At this time, the EQE of the solar cell device is also relatively low. As can be seen from the above analysis, although the overall transmittance of the substrate is improved, the improved spectral range is not consistent with the absorption spectral range of the perovskite material, resulting in no improvement in the efficiency of conventional perovskite solar cell devices.
[0012] To address the aforementioned technical problems, this application provides a novel perovskite solar cell and its fabrication method. The structure of the novel perovskite solar cell is as follows: Figure 3 As shown, Figure 3This is a schematic diagram of a novel perovskite solar cell provided in an embodiment of this application. The novel perovskite solar cell includes, sequentially arranged, an antireflection coating stack, a glass substrate, an equivalent refractive layer, a hole transport layer, a perovskite layer, an electron transport layer, and a top electrode. The antireflection spectral range of the antireflection coating stack is related to the absorption spectral range of the perovskite layer. The antireflection coating stack is used to construct a refractive index transition between air and the glass substrate, increasing the transmittance of effective light within the absorption spectral range of natural light through a first interface, which is the interface between the antireflection coating stack and the glass substrate. The target equivalent refractive index of the equivalent refractive layer is related to the first refractive index of the glass substrate and the second refractive index of the hole transport layer. The equivalent refractive layer is used to construct a refractive index transition between the glass substrate and the hole transport layer, reducing the reflectivity of incident light through a second interface, where the incident light is light that passes through the glass substrate and enters the equivalent refractive layer. The second interface is the interface between the equivalent refractive layer and the hole transport layer.
[0013] The antireflection spectral range of the antireflection coating stack is related to the absorption spectral range of the perovskite layer. In some embodiments, the antireflection spectral range is the same as the absorption spectral range. The antireflection coating stack targets the absorption spectral range of the perovskite layer to increase the transmittance of only the light that the perovskite can effectively absorb, rather than indiscriminately increasing the full spectrum of light.
[0014] For example, perovskite materials typically have a bandgap of 1.48 eV-1.56 eV and an absorption spectrum of 680 nm-810 nm. Therefore, the antireflection spectrum is 680 nm-810 nm. The antireflection coating mainly enhances the light transmission in the 680 nm-810 nm range. The antireflection coating is deposited on the first side of the glass substrate using a PVD process. Unlike conventional antireflection peaks at 550 nm and a decrease in optical transmittance after 600 nm, the antireflection peak of the antireflection coating deposited in this application is biased towards red light. This ensures high transmittance in the 680 nm-810 nm spectral range.
[0015] The method for achieving antireflection through antireflection coating stacking is as follows: by constructing a refractive index transition between air and glass substrate through antireflection coating stacking, reflection caused by abrupt changes in the refractive index between air and glass is avoided, and the transmittance of effective light in the absorption spectrum range through the first interface is increased. The first interface refers to the interface between the antireflection coating stacking and the glass substrate.
[0016] The equivalent refractive layer is used to construct the refractive index transition between the glass substrate and the hole transport layer, avoiding light reflection loss at the interface between the two and ensuring that the light transmitted through the glass enters the perovskite layer efficiently.
[0017] The equivalent refractive layer reduces reflection loss by designing the target equivalent refractive index of the equivalent refractive layer to construct a smooth refractive index gradient between the glass substrate, the equivalent refractive layer, and the hole transport layer, thereby reducing the reflection of incident light through the second interface. The incident light is the light that passes through the glass substrate and enters the equivalent refractive layer. The second interface is the interface between the equivalent refractive layer and the hole transport layer.
[0018] Furthermore, in some embodiments, the second refractive index is associated with the fifth refractive index of the perovskite layer, and the difference between the second refractive index and the fifth refractive index is less than a preset difference, which is set based on reducing interface light reflection and improving the light absorption efficiency of the perovskite layer.
[0019] In this design, the second refractive index of the hole transport layer is related to the fifth refractive index of the perovskite layer. In some embodiments, the second and fifth refractive indices are nearly identical, and the difference between them is less than a preset difference. This preset difference is set based on reducing interface light reflection and improving the light absorption efficiency of the perovskite layer. Theoretically, the preset difference can be zero, but it can be adjusted according to the manufacturing process and actual needs. The near-identical refractive index of the hole transport layer and the perovskite layer can further effectively reduce the reflection loss of light entering the perovskite layer from the hole transport layer.
[0020] Please see Figure 4 , Figure 4 This is a schematic diagram of the optical path of the novel perovskite solar cell provided in the embodiments of this application, as shown below. Figure 4 As shown, before entering the perovskite layer, natural light E0 passes through an antireflection coating layer. This layer effectively reduces the reflectivity of the incoming light, resulting in a reflectivity E1´≈0.5%, thus ensuring the absolute amount of light entering the battery module. When the light passes through the glass substrate into the equivalent refractive layer, the target equivalent refractive index of the equivalent refractive layer can be adjusted based on the actual refractive indices of the glass substrate and the hole transport layer, thereby minimizing light reflection. Simultaneously, during the PVD deposition of the hole transport layer material, the refractive index of the hole transport layer is adjusted by modifying the oxygen flow rate, sputtering pressure, and annealing process, ensuring that the refractive index of the hole transport layer is essentially the same as that of the perovskite layer. This effectively reduces the reflectivity E2´ at the interface between the hole transport layer and the perovskite layer. Thus, the total reflectivity of the new structure is E´=E1´+E2´.
[0021] Please see Figure 5 , Figure 5 This is a schematic diagram of the optical path of a conventional perovskite solar cell provided in an embodiment of this application, such as... Figure 5As shown, natural light E0 enters the perovskite layer after passing through the glass substrate. Before being absorbed by the perovskite layer, natural light propagates between different materials, and there will be a certain amount of reflected light when it passes through each interface. The actual reflected light E” = E1” + E2” + E3” + E4”. According to the test, E1” ≈ 4.2%. The actual reflectivity of other reflective interfaces is expected to be between 1.5% and 2.5% depending on the actual refractive index data. Therefore, natural light is greatly weakened before entering the perovskite layer, which will definitely affect the power generation efficiency of the module.
[0022] It can be seen that, compared to Figure 5 The novel perovskite cell structure provided in this application can effectively reduce the reflectivity of perovskite devices and improve the power generation efficiency of battery devices, compared with the conventional perovskite cell shown.
[0023] Please see Figure 6 , Figure 6 This image shows a comparison of the EQE and optical transmittance of the perovskite material before and after antireflection treatment for the novel perovskite solar cell provided in this application. The process flow for the novel perovskite solar cell structure is compatible with existing equipment, and the added PVD coating process can also utilize existing equipment. Both the antireflection film stack and the equivalent refractive layer can be deposited using the PVD method. Unlike the antireflection film structure in the prior art, the optimized test data is as follows... Figure 6 As shown, the antireflection peak of the antireflection coating stack in this application is in the range of 610nm-630nm, and it also exhibits excellent transmittance in the spectral range of 500nm-900nm. This ensures the EQE absorption efficiency of the perovskite material in red and near-infrared light, making the spectral antireflection range and the effective absorption band of the perovskite material the same. Testing shows that the improved EQE absorption rate, while maintaining a stable perovskite cell layer process, can increase the efficiency of the cell device by approximately 5%-8%.
[0024] As can be seen, in this embodiment, the novel perovskite solar cell includes an antireflection film stack, a glass substrate, an equivalent refractive layer, a hole transport layer, a perovskite layer, an electron transport layer, and a top electrode arranged sequentially. The antireflection spectral range of the antireflection film stack is related to the absorption spectral range of the perovskite layer. The antireflection film stack is used to construct a refractive index transition between air and the glass substrate, increasing the transmittance of effective light within the absorption spectral range of natural light through a first interface, which is the interface between the antireflection film stack and the glass substrate. The target equivalent refractive index of the equivalent refractive layer is related to the first refractive index of the glass substrate and the second refractive index of the hole transport layer. The equivalent refractive layer is used to construct a refractive index transition between the glass substrate and the hole transport layer, reducing the reflectivity of incident light through a second interface, where the incident light is the light that passes through the glass substrate and enters the equivalent refractive layer. The second interface is the interface between the equivalent refractive layer and the hole transport layer. As can be seen, compared with the existing structure, this application increases the absolute amount of effective light entering the battery by stacking antireflective coatings. At the same time, it reduces the interface reflection loss of the perovskite battery by using an equivalent refractive layer, ensuring that incident light passing through the glass substrate can penetrate to the perovskite layer without significant loss. Through the superposition of these two designs, the utilization rate of light in the battery can be effectively improved, thereby improving the power generation efficiency of the battery.
[0025] In some embodiments, the antireflective coating stack is formed by alternating layers of high-refractive-index materials and low-refractive-index materials.
[0026] In some embodiments, the antireflective coating stack is deposited on the first surface of the glass substrate using a PVD process, and the film structure of the antireflective coating stack is SiO2+(Si3N4+SiO2). n Wherein, SiO2 is the low refractive index material, Si3N4 is the high refractive index material, and n is an integer greater than or equal to 2.
[0027] See Figure 8 The antireflective coating stack adopts a structure formed by alternating layers of high-refractive-index and low-refractive-index materials, specifically the film structure is SiO2+(Si3N4+SiO2). n (n is an integer greater than or equal to 2), where SiO2 is a low refractive index material (refractive index approximately 1.46) and Si3N4 is a high refractive index material (refractive index approximately 2.0-2.2), and they are deposited on the first surface of the glass substrate (i.e., the light incident side surface) using PVD (physical vapor deposition) technology. The underlying principle of this structural design is based on the "thin-film interference antireflection effect": when natural light from air (refractive index approximately 1.0) is incident on the antireflection film stack, reflected light is generated at the upper and lower interfaces of each thin film. Through the periodic alternation of high / low refractive index materials, the phase difference of the reflected light at different interfaces can satisfy the "half-wavelength odd multiple" condition, thereby forming destructive interference, canceling out part of the reflected light energy, and ultimately improving the intensity of transmitted light.
[0028] In practice, the SiO2 layer is placed on the side in contact with air, and its refractive index is closer to that of air, which can reduce interfacial reflection between the antireflection coating and the air; while (Si3N4+SiO2) n The repeating unit gradually bridges the refractive index difference between air and the glass substrate through a step-like gradient. After the SiO2 layer, Si3N4 layers and another SiO2 layer are stacked sequentially. Finally, the SiO2 layer directly contacts the glass substrate (refractive index approximately 1.52). For example, when n=2, the refractive index change from the air side to the glass substrate side is 1.0-1.46-(2.0-1.46)-(2.0-1.46)-1.52. This smooth transition avoids significant reflections caused by abrupt changes in refractive index at a single interface. Furthermore, as the value of n increases (e.g., n=3), the refractive index gradient becomes further refined, covering a wider photovoltaic range and adapting to the different absorption characteristics required by the perovskite layer.
[0029] At the fabrication process level, the choice of PVD technology provides a crucial guarantee for the performance of the antireflection coating stack. This process enables nanometer-level precision control of film thickness, ensuring that the optical thickness (the product of refractive index and physical thickness) of each layer precisely matches 1 / 4 of the target wavelength. This is a core condition for the stable realization of the destructive interference effect. Simultaneously, the SiO2 and Si3N4 films prepared by PVD have high density and good surface uniformity, reducing light scattering losses caused by internal pores or impurities, thus ensuring the consistency of the interference effect. Furthermore, this process is suitable for large-area deposition of inorganic non-metallic materials, exhibits strong adhesion to glass substrates, and is directly compatible with existing photovoltaic glass coating production lines, laying the foundation for subsequent industrial applications.
[0030] Understandably, the choice of the n value can be dynamically adjusted according to the width of the perovskite layer's absorption spectrum: for narrow bandgap perovskites (absorption peaks concentrated in the 750nm-800nm range), n=2 is sufficient to meet the anti-reflection requirements; for wide bandgap perovskites (absorption range extended to 400nm-700nm), n can be increased to 3, refining the refractive index gradient through more alternating layers and widening the anti-reflection range. Regarding material substitution, if further improvement in the film's weather resistance is needed to adapt to harsh applications such as high temperature and high humidity, Si3N4 can be replaced with TiO2 (a high refractive index material, approximately 2.3), and SiO2 can be replaced with Al2O3 (a low refractive index material, approximately 1.6). Only the thickness parameters of each layer need to be adjusted synchronously to maintain the destructive interference conditions, thus preserving the anti-reflection effect. Furthermore, the design concept of this antireflective coating stack can be extended to other photovoltaic devices (such as crystalline silicon-perovskite tandem cells). By adjusting the types and structural parameters of high-refractive-index materials / low-refractive-index materials, the absorption characteristics of different active layers can be adapted, providing a general solution for optical optimization of various types of photovoltaic devices.
[0031] As can be seen, in this embodiment, the antireflection film stack can first significantly improve the transmittance of the perovskite layer in the absorption spectral range. Through precise interference design, the light reflectance in the absorption spectral range can be directly increased to increase the number of effective photons entering the battery, providing a sufficient source for the generation of charge carriers in the perovskite layer. Secondly, the multilayer alternating structure effectively broadens the antireflection spectral range, compared to the limitation of traditional single-layer antireflection films that can only achieve antireflection at a single wavelength. (Si3N4+SiO2) n The structure (n≥2) allows for adjustments to the number and thickness of each layer, ensuring the antireflection range covers the main absorption bands of the perovskite layer (e.g., 400-800nm), avoiding excessive reflection of light in certain absorption bands due to an overly narrow antireflection range. Furthermore, the stability and reliability of the film are significantly enhanced. The SiO2 and Si3N4 films prepared by PVD exhibit excellent chemical stability, resistance to water and UV aging, protecting the glass substrate from environmental corrosion and reducing the risk of film peeling during long-term use, thus extending device lifespan. Finally, this antireflection film stack and the subsequent equivalent refractive layer create an optical synergy: the antireflection film stack ensures more effective light enters the glass substrate, while the equivalent refractive layer further reduces interface reflection between the glass substrate and the hole transport layer. The combination of these two elements reduces the total light transmission loss in the "air-glass-perovskite layer" process, providing crucial support for improving the device's photoelectric conversion efficiency.
[0032] In some embodiments, the target equivalent refractive index is a value between the first refractive index and the second refractive index.
[0033] There is a significant difference between the first refractive index of the glass substrate and the second refractive index of the hole transport layer. By setting the target equivalent refractive index of the equivalent refractive layer to be between the first and second refractive indices, a smooth refractive index transition range can be constructed, fundamentally reducing reflection loss.
[0034] To achieve this goal, the equivalent refractive layer adopts a layered architecture. In some embodiments, the equivalent refractive layer includes a SiO2 layer, a matching layer, an adjustment layer, and a bottom electrode arranged sequentially. The matching layer is connected to the glass substrate through the SiO2 layer. The third refractive index of the matching layer is a value between the first refractive index and the second refractive index. The fourth refractive index of the adjustment layer is controlled by the thickness of the adjustment layer. The adjustment layer is used to compensate for the difference between the actual equivalent refractive index and the target equivalent refractive index of the equivalent refractive layer, so that the actual equivalent refractive index approaches the target equivalent refractive index.
[0035] Among them, see Figure 8 The equivalent refractive layer consists of a SiO2 layer, a matching layer, a regulating layer, and a bottom electrode arranged sequentially. Each layer works synergistically through functional division of labor. As the underlying bonding structure, the SiO2 layer is in direct contact with the glass substrate at one end. Its refractive index is closer to the first refractive index of the glass substrate, which can reduce the reflection at the initial interface between the glass substrate and the equivalent refractive layer. In addition, the SiO2 layer forms covalent bonds with the Si=O unsaturated bonds on the surface of the glass substrate, which improves the adhesion of the film. At the same time, because the deposited SiO2 underlayer is relatively rough at the microscopic level, it can improve the adhesion between the two when the matching layer is deposited in the subsequent process, and prevent the film from peeling off due to material properties.
[0036] The matching layer serves as a "basic transition" layer. Its third refractive index is also between the first and second refractive indices. Through its own refractive index characteristics, it builds a preliminary optical bridge between the glass substrate and the hole transport layer, laying the foundation for subsequent precise control.
[0037] The fourth refractive index of the adjustment layer can be controlled by adjusting the thickness parameter. Its core function is to compensate for the difference between the actual equivalent refractive index and the target equivalent refractive index of the equivalent refractive layer. Since the refractive index of each film layer may have slight deviations due to process fluctuations during actual preparation, it is difficult to completely achieve the target value of the overall equivalent refractive index by using only the SiO2 layer and the matching layer. However, the adjustment layer can change its contribution weight to the overall equivalent refractive index by increasing or decreasing its thickness, and finally make the actual equivalent refractive index approach the target equivalent refractive index. The bottom electrode, while ensuring conductivity, ensures optical transparency through material selection (such as ITO, i.e., transparent conductive oxide), and avoids light transmission obstruction due to the presence of the electrode.
[0038] For example, if the second refractive index of the hole transport layer is between 2.1 and 2.52, and the first refractive index of the glass substrate is about 1.52, then the range of the third refractive index of the matching layer is 1.52 to (2.1-2.52).
[0039] In some embodiments, the actual equivalent refractive index is calculated based on the refractive index and thickness of the SiO2 layer, the matching layer, the adjustment layer, and the bottom electrode, respectively.
[0040] In the calculation of the actual equivalent refractive index, the value is not the refractive index of a single film layer, but is calculated together based on the refractive indices and thicknesses of the SiO2 layer, matching layer, adjustment layer and bottom electrode. This is because the thickness of different film layers will affect the propagation path and phase of light within the layer, thereby changing the overall equivalent optical effect. Therefore, it is necessary to ensure the accuracy of the actual equivalent refractive index through comprehensive calculation to provide a basis for optimizing the thickness of the adjustment layer.
[0041] In some embodiments, the equivalent refractive layer is deposited on the second side of the glass substrate using a PVD process, and the film structure of the equivalent refractive layer is SiO2+SiON. x+Nb2O5+ITO, where SiO2 is the film material of the SiO2 layer, and SiON... x The matching layer is the film material, Nb2O5 is the film material of the adjustment layer, and ITO is the film material of the bottom electrode. ITO is a transparent conductive oxide. Wherein, x is SiON x The ratio of oxygen (O) atoms to nitrogen (N) atoms in the third refractive index is inversely correlated with the ratio of oxygen (O) atoms to nitrogen (N) atoms.
[0042] In terms of specific film structure and materials, the equivalent refractive layer is deposited on the second side of the glass substrate using PVD technology, and its specific structure is SiO2 + SiON. x +Nb2O5+ITO, each material corresponds to a functional layer: SiO2, as the film material of the SiO2 layer, becomes the optimal choice for bottom-layer bonding due to its stable optical properties and compatibility with glass substrates; SiON x As a matching layer material, its core advantage lies in the adjustability of its refractive index: by changing the SiON... x The ratio of oxygen atoms to nitrogen atoms, x, allows for flexible adjustment of the third refractive index, and x and the third refractive index are inversely related: when x ≥ 1, the larger x is, the lower the third refractive index becomes, tending towards the refractive index of SiO2; when x < 1, the smaller x is, the higher the third refractive index becomes, tending towards the refractive index of Si3N4. This characteristic allows the matching layer to precisely adjust its own third refractive index according to the specific values of the first and second refractive indices, ensuring the adaptability of the basic transition function. Nb2O5, as the adjustment layer material, has the characteristics of high refractive index stability and easy control of thickness adjustment precision, and can reliably realize the compensation function of the actual equivalent refractive index. ITO, as the bottom electrode material, not only has excellent conductivity to meet the electrode function requirements, but also has high transparency, which can ensure the transport of charge carriers without affecting the normal transmission of light, achieving functional compatibility of conductivity and light transmission.
[0043] As can be seen, in this embodiment, the equivalent refractive layer first effectively eliminates the interface reflection loss between the glass substrate and the hole transport layer. Through the precise design of the target equivalent refractive index and the synergistic control of each film layer, the light entering the hole transport layer from the glass substrate no longer experiences significant reflection due to abrupt changes in refractive index, greatly improving the transmission efficiency of incident light and ensuring that more effective light can reach the perovskite layer for absorption. Secondly, the layered control architecture enhances the flexibility and reliability of optical matching: the basic transition between the SiO2 layer and the matching layer ensures the correctness of the overall optical direction, while the compensation function of the adjustment layer solves the deviation problem in actual processes, enabling the equivalent refractive layer to adapt to different batches and parameters of glass substrates and hole transport layers. The transport layer reduces the stringent requirements for upstream materials. Furthermore, the integrated design of the bottom electrode and the optical functional layer achieves synergy between optical transmission and electrical conduction: the choice of ITO material avoids the electrode blocking light and ensures that the charge carriers generated by the perovskite layer can be efficiently transported to the external circuit without functional conflict. Finally, the equivalent refractive layer and the antireflective film stack mentioned above form a synergistic optical optimization along the entire path: the antireflective film stack ensures that more effective light enters the glass substrate, while the equivalent refractive layer ensures that this light efficiently penetrates to the hole transport layer and finally reaches the perovskite layer. Together, they construct a non-reflective "incident-transmission" path, providing a good optical foundation for the light absorption and subsequent photoelectric conversion of the perovskite layer.
[0044] In some embodiments, the film material of the hole transport layer is NiO. y Wherein, y is NiO y The ratio of oxygen (O) atoms to nickel (Ni) atoms, wherein the magnitude of the atomic ratio is positively correlated with the second refractive index.
[0045] The hole transport layer, as the core functional layer connecting the perovskite layer and the bottom electrode in a perovskite solar cell, must not only achieve efficient hole transport generated by the perovskite layer but also form a good optical match with the equivalent refractive layer to avoid light loss due to incompatibility of optical properties. In this embodiment, the hole transport layer is made of NiO. y As a film material, by controlling NiO y The ratio y of oxygen (O) to nickel (Ni) atoms enables precise control of the second refractive index of the hole transport layer, thereby simultaneously meeting the dual requirements of optical matching and carrier transport.
[0046] Among them, the value of y is positively correlated with the second refractive index: as y increases, NiO... y Medium and high valence nickel ions (Ni 3+The increased proportion of nickel ions (Ni) leads to a higher oxygen atom density in the crystal lattice, resulting in enhanced film compactness and increased light refraction, thus raising the second refractive index. When y decreases, the proportion of low-valence nickel ions (Ni) increases. 2+ With an increased proportion of γ, the crystal structure becomes relatively loose, weakening the material's refractive power and correspondingly reducing the second refractive index. This positive correlation between γ and the second refractive index provides a controllable core parameter for the optical matching of the hole transport layer. Combining the previously discussed relationship between the second refractive index of the hole transport layer and the fifth refractive index of the perovskite layer, the value of γ can be adjusted to make the second refractive index and the fifth refractive index nearly identical. Simultaneously, by combining this with the target equivalent refractive index of the equivalent refractive layer, a smooth transition from the target equivalent refractive index to the second refractive index and then to the fifth refractive index can be achieved, resolving the optical mismatch problem between the hole transport layer and the upstream and downstream films.
[0047] In addition, NiO y The design logic of the hole transport layer possesses strong universality and flexibility. In multi-junction perovskite solar cells, the refractive index of the perovskite layer can be adjusted to match a specific second refractive index for each sub-cell (e.g., wide bandgap top cell, narrow bandgap bottom cell) based on the difference in refractive index of the perovskite layer, ensuring uniform light distribution within the multi-junction cell and avoiding efficiency bottlenecks caused by optical mismatch in a particular junction. In perovskite-crystalline silicon tandem solar cells, the value of NiO can be adjusted by controlling the refractive index of the perovskite layer. y The second refractive index of the hole transport layer is adapted to the optical properties of both the perovskite layer and the crystalline silicon substrate, optimizing the light transmission efficiency at the stacked interface and further improving the overall conversion efficiency of the stacked solar cell.
[0048] As can be seen, in this embodiment, NiO y The hole transport layer first adjusts the γ-axis to ensure the second refractive index matches the equivalent refractive layer and the perovskite layer, significantly reducing reflection losses at the equivalent refractive layer-hole transport layer interface and the hole transport layer-perovskite layer interface. This ensures more effective light is absorbed by the perovskite layer, providing sufficient light energy for carrier generation. Secondly, NiO... y The material possesses excellent chemical and thermal stability. Its dense film structure can act as a "protective layer" to inhibit ion migration in the perovskite layer, reduce direct contact between the perovskite layer and the electrode, reduce device performance degradation caused by interfacial reactions, and extend battery life. Finally, the control of y is simple and easy to achieve. The value of y can be precisely controlled by adjusting parameters such as oxygen partial pressure and deposition temperature in the PVD process, without the need for complex material modification or doping. It is compatible with existing perovskite battery mass production processes, lowering the threshold for technology implementation.
[0049] The aforementioned novel perovskite solar cell structure design achieves efficient integration of light absorption and charge carrier transport through the synergistic cooperation of functional layers such as antireflection coatings and equivalent refractive layers. The fabrication method of this novel perovskite solar cell is described in detail below, based on the layered arrangement logic of the cell.
[0050] Please see Figure 7 , Figure 7 The flowchart illustrates the fabrication method of the novel perovskite solar cell provided in this application embodiment, the method comprising the following steps S701-S7013: Step S701: Clean and dry the glass substrate. Step S702: Deposit (SiO2+(Si3N4+SiO2)) on the front side of the glass substrate. n ) membrane, forming an anti-reflection membrane layer; Step S703: Deposit (SiO2++SiON) on the reverse side of the glass substrate. x A Nb2O5+ITO film is formed to create an equivalent refractive layer; Step S704: Perform P1 laser scribing on the glass substrate with the above coating to form the P1 scribing line of the novel perovskite solar cell. Step S705: Clean the glass substrate with the P1 scribed lines and deposit NiO on the equivalent refractive layer. y This forms a hole transport layer; Step S706: After depositing the hole transport layer, test the light transmittance of the current perovskite solar cell in the absorption spectrum range. Step S707: If the light transmittance is greater than or equal to the preset transmittance; Step S708: Deposit a perovskite layer on the hole transport layer; Step S709: Deposit an electron transport layer on the perovskite layer; Step S7010: Perform P2 laser scribing on the glass substrate after depositing the electron transport layer; Step S7011: Fabricate a top electrode on the electron transport layer; Step S7012: After fabricating the top electrode, the glass substrate is sequentially subjected to P3 laser scribing and P4 laser edge cleaning. Step S7013: Photovoltaic module encapsulation is performed on the glass substrate that has undergone P4 laser edge cleaning to obtain a novel perovskite cell.
[0051] Based on the above structure and method, the following three specific embodiments are provided.
[0052] Example 1 An organic-inorganic hybrid perovskite material was selected, and its refractive index was tested to be 2.15. Before PVD coating, the glass substrate was cleaned and dried before being mounted for coating with the mixture SiO2 + (Si3N4 + SiO2)2 + glass + SiO2 + SiON. x +Nb₂O₅+ITO+NiO y : A vertical, fully automated continuous magnetron sputtering coating machine was used to coat the front side of a glass substrate with a SiO2 + (Si3N4 + SiO2)2 film. The coating temperature range was 300℃ to 420℃, and the chamber cycle time was 110 seconds. Three Si targets were used for SiO2 coating, and two Si targets were used for Si3N4 coating. The Si sputtering power was 8000W to 10000W, and the Si3N4 sputtering power was 8500W to 12000W. The O2 flow rate was 100 Sccm to 130 Sccm, the Ar flow rate was 200 Sccm to 220 Sccm, the N2 flow rate was 200 Sccm to 220 Sccm, and the vacuum level was 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa; after the antireflection coating is deposited, the structure is SiO2+(Si3N4+SiO2)2+glass. At this time, the single-sided reflectance of the antireflection coating at 630nm should be ≤0.5%, and the average transmittance in the 600nm-850nm spectral range should be ≥94%. After testing, a vertical fully automatic continuous magnetron sputtering coating machine was used to coat the reverse side of the glass substrate with SiO2 + SiON. x +Nb₂O₅+ITO film, coating temperature setting range: 260℃~380℃, coating chamber cycle time: 130 seconds; SiO₂ film layer is deposited using a single Si target in the first chamber, with Si sputtering power of 6000W~8000W, O₂ flow rate of 100Sccm~130Sccm, Ar flow rate of 200Sccm~220Sccm, and vacuum degree of 3.0×10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa, two Si targets are used in the second chamber to plate SiON. x The film layer has a Si sputtering power of 7000W–11000W, an O2 flow rate of 70Sccm–100Sccm, an N2 flow rate of 80Sccm–110Sccm, an Ar flow rate of 120Sccm–180Sccm, and a vacuum level of 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1Between 1000 W and 12000 W, an Nb2O5 film was deposited in the third chamber using a single Nb2O5 target. The Nb2O5 sputtering power was 9000 W–12000 W, the O2 flow rate was 100 Sccm–130 Sccm, the Ar flow rate was 180 Sccm–240 Sccm, and the vacuum level was 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between 1000 W and 18000 W, an ITO film was deposited using three ITO targets in the fourth chamber. The ITO sputtering power was 9000 W to 18000 W, the O2 flow rate was 100 Sccm to 130 Sccm, the Ar flow rate was 200 Sccm to 220 Sccm, and the vacuum level was 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa, SiO2 + SiON is completed in one step. x The Nb2O5+ITO film was deposited, at which point the structure was SiO2+(Si3N4+SiO2)2+glass+SiO2+SiON. x +Nb2O5+ITO. The total thickness of the antireflective coating on the front side is 450Å-950Å, and the thickness of the ITO film on the back side is 1200Å-1600Å, with a surface resistivity of 10Ω-15Ω.
[0053] The glass substrate with the above coating is then laser-etched to form the P1 scribing line for the photovoltaic solar cell.
[0054] The substrate with P1 marking completed above is cleaned, and then NiO is deposited. y Hole transport layer, coating temperature setting range: 220℃~340℃, coating chamber cycle time: 100 seconds; NiO is coated using a single Ni target. y The film was sputtered with a Ni sputtering power of 4000W–8000W, an O2 flow rate of 100Sccm–130Sccm, an Ar flow rate of 200Sccm–220Sccm, and a vacuum level of 3.5 × 10⁻⁶. -1 Pa ~ 5.5 × 10 -1 Between Pa, NiO y The film thickness is around 20nm, completing the NiO process. y After the film is deposited, the structure is SiO2+(Si3N4+SiO2)2+glass+SiO2+SiON. x +Nb₂O₅+ITO+NiO y Then, the product is annealed at 250℃-320℃ to improve the crystal structure and adjust the NiO content. y Refractive index, at this time NiO y The refractive index is approximately 2.15.
[0055] After the above film deposition was completed, the average transmittance of the substrate at 610nm-810nm was tested to be ≥91%. After the above process was completed, the glass substrate was cut into small particles, and then the perovskite layer, electron transport layer and top electrode were fabricated. The device was then packaged and the power was tested. Compared with the traditional process before the improvement, the efficiency of the device was improved by about 6.3%.
[0056] Example 2 Organic-inorganic hybrid perovskite material was selected, and its refractive index was tested to be 2.23. Before PVD coating, the glass substrate was cleaned and dried before being mounted for coating with SiO2+(Si3N4+SiO2)3+glass+SiO2+SiON. x +Nb₂O₅+ITO+NiO y : A vertical, fully automated continuous magnetron sputtering coating machine was used to coat the front side of a glass substrate with a SiO2+(Si3N4+SiO2)3 film. The coating temperature range was 300℃~420℃, and the chamber cycle time was 110 seconds. Four Si targets were used for SiO2 coating, and three Si targets were used for Si3N4 coating. The Si sputtering power was 8000W~10000W, and the Si3N4 sputtering power was 8500W~12000W. The O2 flow rate was 100Sccm~130Sccm, the Ar flow rate was 200Sccm~220Sccm, the N2 flow rate was 200Sccm~220Sccm, and the vacuum level was 3.0×10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa; after the antireflection coating is deposited, the structure is SiO2+(Si3N4+SiO2)3+glass. At this time, the single-sided reflectance of the antireflection coating at 630nm should be ≤0.4%, and the average transmittance in the 600nm-850nm spectral range should be ≥94.3%.
[0057] After testing, a vertical fully automatic continuous magnetron sputtering coating machine was used to coat the reverse side of the glass substrate with SiO2 + SiON. x +Nb₂O₅+ITO film, coating temperature setting range: 260℃~380℃, coating chamber cycle time: 130 seconds; SiO₂ film layer is deposited using a single Si target in the first chamber, with Si sputtering power of 6000W~8000W, O₂ flow rate of 100Sccm~130Sccm, Ar flow rate of 200Sccm~220Sccm, and vacuum degree of 3.0×10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa, two Si targets are used in the second chamber to plate SiON. xThe film layer has a Si sputtering power of 7000W–11000W, an O2 flow rate of 70Sccm–100Sccm, an N2 flow rate of 80Sccm–110Sccm, an Ar flow rate of 120Sccm–180Sccm, and a vacuum level of 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between 10 Pa and 10 Pa, an Nb₂O₅ film was deposited using a single Nb₂O₅ target in the third chamber. The Nb₂O₅ sputtering power was 9000 W–12000 W, the O₂ flow rate was 100 Sccm–130 Sccm, the Ar flow rate was 180 Sccm–240 Sccm, and the vacuum degree was 3.0 × 10⁻⁶ Pa. -1 Pa ~ 4.5 × 10 -1 Between 1000 W and 18000 W, an ITO film was deposited using three ITO targets in the fourth chamber. The ITO sputtering power was 9000 W to 18000 W, the O2 flow rate was 100 Sccm to 130 Sccm, the Ar flow rate was 200 Sccm to 220 Sccm, and the vacuum level was 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa, SiO2 + SiON is completed in one step. x The Nb2O5+ITO film was deposited, at which point the structure was SiO2+(Si3N4+SiO2)3+glass+SiO2+SiON. x +Nb2O5+ITO. The total thickness of the antireflective coating on the front side is 500Å-1030Å, and the thickness of the ITO film on the back side is 1200Å-1600Å, with a surface resistivity of 10Ω-15Ω.
[0058] The glass substrate with the above coating is then laser-etched to form the P1 scribing line for the photovoltaic solar cell.
[0059] The substrate with P1 marking completed above is cleaned, and then NiO is deposited. y Hole transport layer, coating temperature setting range: 220℃~340℃, coating chamber cycle time: 100 seconds; NiO is coated using a single Ni target. y The film was sputtered with a Ni sputtering power of 4000W–8000W, an O2 flow rate of 100Sccm–130Sccm, an Ar flow rate of 200Sccm–220Sccm, and a vacuum level of 3.5 × 10⁻⁶. -1 Pa ~ 5.5 × 10 -1 Between Pa, NiO y The film thickness is around 20nm, completing the NiO process. y After the film is deposited, the structure is SiO2+(Si3N4+SiO2)3+glass+SiO2+SiON. x +Nb₂O₅+ITO+NiOy Then, the product is annealed at 260℃-350℃ to improve the crystal structure and adjust the NiO content. y Refractive index, at this time NiO y The refractive index is approximately 2.22.
[0060] After the above film deposition was completed, the average transmittance of the substrate at 610nm-810nm was tested to be ≥91%. After the above process was completed, the glass substrate was cut into small particles, and then the perovskite layer, electron transport layer and top electrode were fabricated. The device was then packaged and the power was tested. Compared with the traditional process before the improvement, the efficiency of the device was improved by about 5.9%.
[0061] Example 3 Inorganic hybrid perovskite material was selected, and its refractive index was tested to be 2.31. Before PVD coating, the glass substrate was cleaned and dried before being mounted for coating with SiO2+(Si3N4+SiO2)3+glass+SiO2+SiON. x +Nb₂O₅+ITO+NiO y : A vertical, fully automated continuous magnetron sputtering coating machine was used to coat the front side of a glass substrate with a SiO2+(Si3N4+SiO2)3 film. The coating temperature range was 300℃~420℃, and the chamber cycle time was 110 seconds. Four Si targets were used for SiO2 coating, and three Si targets were used for Si3N4 coating. The Si sputtering power was 8000W~10000W, and the Si3N4 sputtering power was 8500W~12000W. The O2 flow rate was 100Sccm~130Sccm, the Ar flow rate was 200Sccm~220Sccm, the N2 flow rate was 200Sccm~220Sccm, and the vacuum level was 3.0×10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa; after the antireflection coating is deposited, the structure is SiO2+(Si3N4+SiO2)3+glass. At this time, the single-sided reflectance of the antireflection coating at 630nm should be ≤0.4%, and the average transmittance in the 600-850nm spectral range should be ≥94.3%.
[0062] After testing, a vertical fully automatic continuous magnetron sputtering coating machine was used to coat the reverse side of the glass substrate with SiO2 + SiON. x+Nb₂O₅+ITO film, coating temperature setting range: 260℃~380℃, coating chamber cycle time: 130 seconds; SiO₂ film is deposited using a single Si target in the first chamber, with Si sputtering power of 6000W~8000W, O₂ flow rate of 100Sccm~130Sccm, Ar flow rate of 200Sccm~220Sccm, and vacuum degree of 3.0×10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa, two Si targets are used in the second chamber to plate SiON. x The film layer has a Si sputtering power of 7000W–11000W, an O2 flow rate of 70Sccm–100Sccm, an N2 flow rate of 80Sccm–110Sccm, an Ar flow rate of 120Sccm–180Sccm, and a vacuum level of 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between 10 Pa and 10 Pa, an Nb₂O₅ film was deposited using a single Nb₂O₅ target in the third chamber. The Nb₂O₅ sputtering power was 9000 W–12000 W, the O₂ flow rate was 100 Sccm–130 Sccm, the Ar flow rate was 180 Sccm–240 Sccm, and the vacuum degree was 3.0 × 10⁻⁶ Pa. -1 Pa ~ 4.5 × 10 -1 Between 1000 W and 18000 W, an ITO film was deposited using three ITO targets in the fourth chamber. The ITO sputtering power was 9000 W to 18000 W, the O2 flow rate was 100 Sccm to 130 Sccm, the Ar flow rate was 200 Sccm to 220 Sccm, and the vacuum level was 3.0 × 10⁻⁶. -1 Pa ~ 4.5 × 10 -1 Between Pa, SiO2 + SiON is completed in one step. x The Nb2O5+ITO film was deposited, at which point the structure was SiO2+(Si3N4+SiO2)3+glass+SiO2+SiON. x +Nb2O5+ITO. The total thickness of the antireflective coating on the front side is 500Å-1030Å, and the thickness of the ITO film on the back side is 1200Å-1600Å, with a surface resistivity of 10Ω-15Ω.
[0063] The glass substrate with the above coating is then laser-etched to form the P1 scribing line for the photovoltaic solar cell.
[0064] The substrate with P1 marking completed above is cleaned, and then NiO is deposited. y Hole transport layer, coating temperature setting range: 220℃~340℃, coating chamber cycle time: 100 seconds; NiO is coated using a single Ni target. yThe film was sputtered with a Ni sputtering power of 4000W–8000W, an O2 flow rate of 100Sccm–130Sccm, an Ar flow rate of 200Sccm–220Sccm, and a vacuum level of 3.5 × 10⁻⁶. -1 Pa ~ 5.5 × 10 -1 Between Pa, NiO y The film thickness is around 20nm, completing the NiO process. y After the film is deposited, the structure is SiO2+(Si3N4+SiO2)3+glass+SiO2+SiON. x +Nb₂O₅+ITO+NiO y Then, the product is annealed at 260-350℃ to improve the crystal structure and adjust the NiO content. y Refractive index, at this time NiO y The refractive index is approximately 2.28.
[0065] After the above film deposition was completed, the average transmittance of the substrate at 610nm-810nm was tested to be ≥91%. After the above process was completed, the glass substrate was cut into small particles, and then the perovskite layer, electron transport layer and top electrode were fabricated. The device was then packaged and the power was tested. Compared with the traditional process before the improvement, the efficiency of the device was improved by about 4.9%.
[0066] By combining the specific preparation process and test data of the above three embodiments, the feasibility and superiority of this novel perovskite battery technology can be further verified.
[0067] Furthermore, this solution is not limited to the inorganic hybrid perovskite materials and process parameters described in the three embodiments above. At the perovskite material level, if an inorganic perovskite with a narrower band gap (e.g., below 1.45 eV) and a higher refractive index (e.g., 2.35-2.40) is selected, the SiON process can be adjusted... x The oxygen-to-nitrogen atomic ratio x (reducing x to increase SiON) x The refractive index is optimized, and the thickness of the Nb2O5 adjustment layer is increased to compensate for the equivalent refractive index deviation, ensuring that the target equivalent refractive index of the equivalent refractive layer can still adapt to the new perovskite refractive index. In terms of process adaptability, the vertical fully automatic continuous magnetron sputtering coating machine and laser scribing equipment used in this solution are commonly used equipment in the photovoltaic industry for mass production. Large-scale production can be achieved without adding new dedicated equipment, and all process parameters (such as sputtering power 8000W~10000W and coating temperature 260℃~380℃) are within the normal operating range of the equipment, without any issues of increased process difficulty or cost, demonstrating strong industrial adaptability. Furthermore, this technical solution can be extended to perovskite-crystalline silicon tandem solar cells, using the glass substrate + antireflective coating + equivalent refractive layer structure of this solution as the top cell substrate of the tandem cell, by adjusting the NiO...y The refractive index of the hole transport layer is adapted to the optical requirements of the tandem interface, further improving the overall light absorption efficiency of the tandem solar cell and expanding the application scenarios of the technology.
[0068] It should also be noted that the process parameters and material selection in this technical solution can be reasonably adjusted according to actual needs, and are not limited to the range described in the above three embodiments: for example, the number of repeating units n of the front antireflection film can be adjusted between 2 and 4 (when n=4, the antireflection spectrum can be further broadened to 550nm-900nm), the number of ITO targets can be adjusted to 2-4 according to the coating rate requirements (without affecting the film surface resistance and transmittance), NiO y The film thickness can fluctuate within the range of 18nm-22nm (while still ensuring the precision of refractive index control and hole transport efficiency). These adjustments all fall within the protection scope of this technical solution, as long as they adhere to the principles of "antireflection film adapted to perovskite absorption spectrum, equivalent refractive layer connecting the refractive index of glass and hole transport layer, and NiO..." y The core design logic of "layer matching perovskite refractive index" can improve device efficiency.
[0069] In summary, this novel perovskite solar cell effectively solves the technical pain points of traditional perovskite solar cells, such as high light reflection loss, optical-electrical performance conflict, and poor process compatibility, through a multi-layer optical collaborative design of "front-side antireflection - back-side transition - hole layer matching" combined with precise and controllable PVD coating process and annealing control methods.
[0070] Unless otherwise stated, all terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. All patents and publications referenced in this application are incorporated herein by reference in their entirety. The terms "comprising" or "including" are open-ended expressions, meaning they include the contents specified in this application but do not exclude other contents.
[0071] In the description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0072] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes and modifications to the above embodiments within the scope of this application.
Claims
1. A novel perovskite solar cell, characterized in that, It includes, in sequence, an antireflective coating stack, a glass substrate, an equivalent refractive layer, a hole transport layer, a perovskite layer, an electron transport layer, and a top electrode. The antireflection spectral range of the antireflection film stack is related to the absorption spectral range of the perovskite layer. The antireflection film stack is used to construct a refractive index transition between air and glass substrate, and to increase the transmittance of effective light in the absorption spectral range in natural light through the first interface, which is the interface between the antireflection film stack and the glass substrate. The target equivalent refractive index of the equivalent refractive layer is related to the first refractive index of the glass substrate and the second refractive index of the hole transport layer. The equivalent refractive layer is used to construct a refractive index transition between the glass substrate and the hole transport layer, and to reduce the reflectivity of incident light passing through the second interface. The incident light is the light that passes through the glass substrate and enters the equivalent refractive layer. The second interface is the interface between the equivalent refractive layer and the hole transport layer.
2. The novel perovskite battery according to claim 1, characterized in that, The antireflective coating is formed by alternating layers of high-refractive-index and low-refractive-index materials.
3. The novel perovskite battery according to claim 2, characterized in that, The antireflective coating stack is deposited on the first surface of the glass substrate using a PVD process, and the film structure of the antireflective coating stack is SiO2+(Si3N4+SiO2). n Wherein, SiO2 is the low refractive index material, Si3N4 is the high refractive index material, and n is an integer greater than or equal to 2.
4. The novel perovskite battery according to claim 1, characterized in that, The target equivalent refractive index is a value between the first refractive index and the second refractive index.
5. The novel perovskite battery according to claim 4, characterized in that, The equivalent refractive layer comprises a SiO2 layer, a matching layer, an adjustment layer, and a bottom electrode arranged sequentially. The matching layer is connected to the glass substrate through the SiO2 layer. The third refractive index of the matching layer is a value between the first refractive index and the second refractive index; The fourth refractive index of the adjustment layer is controlled by the thickness of the adjustment layer. The adjustment layer is used to compensate for the difference between the actual equivalent refractive index and the target equivalent refractive index of the equivalent refractive layer, so that the actual equivalent refractive index approaches the target equivalent refractive index.
6. The novel perovskite battery according to claim 5, characterized in that, The actual equivalent refractive index is calculated based on the refractive index and thickness of the SiO2 layer, the matching layer, the adjustment layer, and the bottom electrode.
7. The novel perovskite battery according to claim 5, characterized in that, The equivalent refractive layer is deposited on the second surface of the glass substrate using a PVD process, and the film structure of the equivalent refractive layer is SiO2+SiON. x +Nb2O5+ITO, where SiO2 is the film material of the SiO2 layer, and SiON... x The matching layer is the film material, Nb2O5 is the film material of the adjustment layer, and ITO is the film material of the bottom electrode. ITO is a transparent conductive oxide. Wherein, x is SiON x The ratio of oxygen (O) atoms to nitrogen (N) atoms in the third refractive index is inversely correlated with the ratio of oxygen (O) atoms to nitrogen (N) atoms.
8. The novel perovskite battery according to claim 1, characterized in that, The second refractive index is related to the fifth refractive index of the perovskite layer. The difference between the second refractive index and the fifth refractive index is less than a preset difference, which is set based on reducing interface light reflection and improving the light absorption efficiency of the perovskite layer.
9. The novel perovskite battery according to claim 8, characterized in that, The hole transport layer is made of NiO. y Wherein, y is NiO y The ratio of oxygen (O) atoms to nickel (Ni) atoms, wherein the magnitude of the atomic ratio is positively correlated with the second refractive index.
10. A method for preparing a novel perovskite solar cell as described in any one of claims 1-9, characterized in that, The method includes: The glass substrate is cleaned and dried. (SiO2+(Si3N4+SiO2)) is deposited on the front side of the glass substrate. n ) membrane, forming an anti-reflection membrane layer; (SiO2+SiON) is deposited on the reverse side of the glass substrate. x A Nb2O5+ITO film is formed to create an equivalent refractive layer; The glass substrate with the above coating is then subjected to P1 laser scribing to form the P1 scribing lines of a novel perovskite solar cell. The glass substrate with the P1 scribed lines completed is cleaned, and NiO is deposited on the equivalent refractive layer. y This forms a hole transport layer; After the hole transport layer was deposited, the light transmittance of the current perovskite solar cell in the absorption spectrum range was tested. If the light transmittance is greater than or equal to the preset transmittance; Deposit a perovskite layer on the hole transport layer; Deposit an electron transport layer on the perovskite layer; P2 laser scribing is performed on the glass substrate after the electron transport layer has been deposited; A top electrode is fabricated on the electron transport layer; After the top electrode is fabricated, the glass substrate is sequentially scribing with P3 laser and cleaning with P4 laser. A novel perovskite solar cell was obtained by encapsulating a glass substrate that had undergone P4 laser edge cleaning into a photovoltaic module.
Citation Information
Cited By
Laminated cell, preparation method and preparation device thereof, and photovoltaic module
CN122094300A
